Louisiana: Crossroads of the Atlantic World - CÃ‰CILE VIDAL (University of Pennsylvania Press, 2013)
â€œPerros los Francesesâ€ are the words that Antoine Paul, a domestic slave, would have cried out to the Sieur RiviÃ¨re, a merchant in New Orleans, on one street of the Louisiana capital on a Sunday afternoon in 1766. Witnesses, some neighbors who watched the fight, told the judge that the Sieur RiviÃ¨re was hitting the slave with a stick and that Antoine Paul was trying to defend himself while â€œchattering incessantly.â€ None of them understood what the slave was saying, because he spoke in Spanish. The Sieur RiviÃ¨re complained that Antoine Paul not only tried to defend himself but also attacked him. Coughing and spitting on the ground, the slave would have made â€œmany silly remarks about the French.â€ In front of the magistrate, Antoine Paul claimed that he did not insult the French; he only said â€œthat the English were dogs, that they did not know the Virgin Mary or anything else, and that the Sieur RiviÃ¨re did not understand correctly if he believed that it was about the French that he talked, that he had nothing wrong to say about them since he was himself a Creole from Martinique.â€ During his first questioning, the defendant had told the judge his complex peregrinations since his birth in Martinique: Dutch merchants bought him and took him to Curacao and then Santo Domingo, where he was baptized. Afterward he circulated in the Caribbean Sea and the Gulf of Mexico, living in various Spanish settlements, before landing in Havana where his current master, Mr. de Loyola, purchased him. The French, the English, the Spaniards in an enslaved man of Africa descentâ€™s view . . . The incident happened while Louisiana, a colony founded by the French in 1699, had been divided and given to Spain and Great Britain by the treaties of Fontainebleau and Paris in 1762â€“1763. Antoine Paulâ€™s owner,Joseph de Loyola, was probably the war commissioner who, a few months earlier, had come from Havana to New Orleans with the new Spanish governor Antonio de Ulloa to take possession of the Louisiana capital and the western bank of the Mississippi River.1 Located at the junction of North America and the Caribbean and at the crossroads of the three main empires that established colonies in the New World, Louisiana experienced a succession of sovereignties in the eighteenth and nineteenth centuries. The lives of Louisianaâ€™s inhabitants, whether they were Native Americans, European settlers, or slaves of African descent, were all impacted by this geography and history, and the conflict involving Antoine Paul was emblematic in this regard. â€œTensions of empiresâ€2 â€” between metropole and colonies, within colonial societies, and among various empiresâ€” and trans- imperial crossings and mobilitiesâ€” especially the slave trade, which was the most internationalized Atlantic commerceâ€” were not abstract realities for these various historical actors. These conflicts deeply shaped life trajectories and informed social identities. Louisianaâ€™s peculiar geography and history, which makes the â€œMississippi colonyâ€ (as Louisiana was known in eighteenth- century France) a paradigmatic case study, calls for an Atlantic perspective.